PEMANFAATAN APLIKASI TIKTOK SEBAGAI MEDIA PEMBELAJARAN BIOLOGI DI SMK FARMASI YAMASI MAKASSAR - Rezki Amalia; Ismail; Hamka Lodang; Oslan Jumadi; Andi Mu'nisa (Jurusan Matematika FMIPA UNM, 2024)
Abstract. The activity of using the TikTok application was carried out at the Yamasi Pharmacy Vocational School, Makassar, which aimed to explain how to use the TikTok application for the learning process in class. This activity uses qualitative descriptive methods. TikTok is a major subject in learning, and its focus is on using such applications as a medium for learning processes. This information is collected through descriptive analysis methods that use journals as sources of information. Data analysis consists of data reduction, data delivery, and conclusion drawing. The results show that the use of the TikTok application, in addition to strategies of exploitation and idealization, can be beneficial as an interactive and exciting learning method. The TikTok application is suitable for learning activities because it is easy to use and has many functions, so the TikToks application can be applied to learning activities. Keywords: Media; Learn; TikTok App